Implementasi teori belajar kognitif dalam pembelajaran Qowaidul Imla’ pada mahasiswa Pendidikan Bahasa Arab UIN Fatmawati Sukarno Bengkulu - Afriansyah, Dibi (MAN 4 Kota Pekanbaru, 2025)
This study explores the implementation of cognitive learning theory in teaching Qowaidul Imla’, particularly within the context of Arabic instruction for non-native speakers. Adopting an axiomatic approach that integrates linguistic and learning theories, the research emphasizes that successful language acquisition depends significantly on an in-depth understanding of both the nature of language and the mental processes involved in learning. Cognitive theory posits that learners actively construct knowledge through cognitive processes such as chunking, scaffolding, and retrieval practice. At UIN Fatmawati Sukarno Bengkulu, the application of this approach in Qowaidul Imla’ instruction led to a marked improvement in students’ comprehension and writing abilities. Rather than simply delivering technical rules, lecturers encouraged students to grasp the underlying logic of Arabic orthographic structures. The use of cognitive strategies also enhanced learners’ confidence, engagement, and reflective capacity in addressing writing errors. Thus, cognitive theory not only offers a robust conceptual foundation for instructional design but also contributes meaningfully to creating Arabic language learning that is meaningful, contextualized, and aligned with how the human mind processes information.